A porous composite foil, a positive electrode sheet, a negative electrode sheet, a semi-solid lithium ion battery and a preparation method thereof
By introducing a mixed primer layer on the surface of the porous composite foil current collector, a complete ion and electron transport channel is constructed, which solves the problem of large internal resistance of the composite foil and improves the energy density and safety performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202211367853.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-11-03
AI Technical Summary
The existing composite foils have problems with large internal resistance and poor rate performance in lithium batteries, which leads to limited energy density and safety performance of the battery.
Porous composite foil collector, including polymer insulating layer and two metal conductive layers, and a mixed primer layer containing conductive agent and inorganic oxide solid electrolyte are introduced on its surface to improve the bonding of active materials and current collectors. Focus on building a complete ion and electron transport channel.
By reducing the internal resistance of the battery, the efficiency of electronic conduction and lithium ions migration is improved, the battery polarization is suppressed, the thermal effect is reduced, the rate performance is improved, and the battery's safety performance is improved by reducing the amount of liquid electrolyte.
Smart Images

Figure CN115832195B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a porous composite foil, a positive electrode sheet, a negative electrode sheet, a semi-solid lithium ion battery and a preparation method thereof. Background Art
[0002] The rapid development of electric vehicles and large-scale energy storage has put forward higher requirements on battery safety and energy density.
[0003] In terms of energy density, the energy density of the battery determines the endurance of electric vehicles, including volume energy density and mass energy density. The positive and negative electrode materials are active energy storage materials for lithium batteries. Aluminum foil and copper foil are both carriers of positive and negative electrode active materials and collectors and conductors of positive and negative electrode electrons. The improvement of battery energy density is achieved by increasing the unit gram capacity of positive electrode active materials on the one hand and reducing the weight of inactive substances on the other. The weight reduction of foil can further improve the energy density of the battery.
[0004] In terms of safety, traditional lithium-ion batteries use organic liquid electrolytes. Therefore, when overcharging, internal short circuit or other abnormal operating conditions occur, the large amount of heat generated will cause the electrolyte to vaporize quickly and the positive electrode material to release oxygen, which may cause safety problems such as battery explosion and electric vehicle fire and spontaneous combustion.
[0005] At present, PET (polyethylene terephthalate) composite aluminum foil and copper foil have the characteristics of low density, thin thickness, high tensile strength, etc., and its good conductivity makes it a good alternative material for traditional lithium battery collectors (aluminum foil and copper foil). When part of the metal is replaced by polymer, PET composite foil can reduce the weight of the material, thereby increasing the energy density of the battery.
[0006] Currently, lithium battery foil is gradually developing towards the direction of being extremely thin. The thinner the lithium battery foil is, the more likely it is to have problems such as tearing, breaking, and wrinkling, posing a huge challenge to the safety of the battery cell. PET composite foil has the characteristics of a thin conductive layer and a non-conductive base film, which makes it easier to be melted when an internal short circuit occurs in a lithium battery, thereby cutting off the short-circuit current, reducing the heat generated during a short circuit, preventing thermal runaway, and improving the safety performance of the battery. In addition, the amount of metal used in PET composite foil is only 1 / 3-1 / 5 of the original pure metal foil. If the manufacturing cost can be controlled, the theoretical cost of the composite foil will be lower than that of the metal foil, and there is a large room for cost reduction of the material.
[0007] However, since the current composite foils are all made of micron-sized composite foils with a "sandwich" structure of "metal layer-polymer layer-metal layer", and the polymer material layer is used in the middle, this insulating layer makes it impossible for the metal coatings on both sides to achieve electronic conduction, the current conduction in the battery is hindered, resulting in a large internal resistance of the battery, which affects the battery's rate performance.
[0008] Therefore, there is an urgent need to develop a technology that can solve the above technical problems. Summary of the invention
[0009] The purpose of the present invention is to provide a porous composite foil, a positive electrode sheet, a negative electrode sheet and a semi-solid lithium ion battery and a preparation method thereof in view of the technical defects existing in the prior art.
[0010] To this end, the present invention provides a porous composite foil material for use in a battery pole piece, which includes a porous composite foil material current collector;
[0011] A porous composite foil current collector includes a polymer insulating layer and two metal conductive layers;
[0012] A layer of the metal conductive layer is respectively provided on the upper and lower sides of the polymer insulating layer;
[0013] A plurality of through holes are arranged through the porous composite foil current collector;
[0014] The outer side surface of each metal conductive layer in the porous composite foil current collector is coated with a mixed primer layer.
[0015] Preferably, when the porous composite foil current collector is used in the positive electrode sheet, the two metal conductive layers are both aluminum foils, and the porous composite foil current collector at this time is defined as a composite porous aluminum foil current collector;
[0016] When the porous composite foil current collector is used in the negative electrode plate, the two metal conductive layers are both copper foils, and the porous composite foil current collector at this time is defined as a composite porous copper foil current collector.
[0017] Preferably, the thickness of the polymer insulating layer is 2-10 μm;
[0018] The thickness of each metal conductive layer is 1-5 μm;
[0019] The pore size of the through hole is between 0.2-3 μm;
[0020] The porosity of the porous composite foil current collector is 10%-40%;
[0021] The thickness of each mixed primer layer is 2-10 microns.
[0022] Preferably, the material of the polymer insulating layer includes any one of polyethylene, polypropylene, polyvinyl chloride, polyimide, polyacrylonitrile and polyethylene terephthalate;
[0023] The mixed primer layer comprises the following components expressed in percentage by mass:
[0024] 10%-40% conductive agent, 50%-85% oxide solid electrolyte and 5%-10% binder;
[0025] For the hybrid primer layer, the conductive agent includes at least one of carbon black, Ketjen black, conductive graphite, conductive fiber, carbon nanotubes, and graphene;
[0026] An oxide solid electrolyte comprising at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide and lithium lanthanum zirconium thallium oxide;
[0027] The binder includes one or a mixture of two or more of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene-butadiene rubber, hydroxypropyl methylcellulose, carboxystyrene-butadiene latex and polyvinyl alcohol.
[0028] In addition, the present invention provides a positive electrode sheet, comprising the porous composite foil as described above;
[0029] The outer side of each mixed primer layer in the porous composite foil is coated with a positive electrode material layer;
[0030] A positive electrode material layer, including a positive electrode active material, an oxide solid electrolyte, a conductive agent and a binder;
[0031] The mass ratio of the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (84-96):(1-5):(1-5):(2-6);
[0032] For the positive electrode material layer, the positive electrode active material specifically includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate and lithium manganese iron phosphate;
[0033] The conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers and graphene;
[0034] The oxide solid electrolyte includes at least one of LATP, LAGP, LLZO, LLTO and LLZTO;
[0035] The binder includes at least one of PVDF, SBR, CMC and PTFE.
[0036] In addition, the present invention provides a negative electrode plate, comprising the porous composite foil as described above;
[0037] The outer side of each mixed primer layer in the porous composite foil is coated with a negative electrode material layer;
[0038] A negative electrode material layer, including a negative electrode active material, an oxide solid electrolyte, a conductive agent and a binder;
[0039] The mass ratio of the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (83-97):(1-5):(1-5):(1-7);
[0040] Wherein, for the negative electrode material layer, the negative electrode active material includes one or more of silicon, silicon dioxide, silicon oxide, artificial graphite, natural graphite, composite graphite, soft carbon and hard carbon;
[0041] For the negative electrode material layer, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers and graphene;
[0042] For the negative electrode material layer, the oxide solid electrolyte includes at least one of LATP, LAGP, LLZO, LLTO and LLZTO;
[0043] For the negative electrode material layer, the binder includes any one of SBR, PAA and PTFE.
[0044] In addition, the present invention also provides a semi-solid lithium-ion battery, which includes a battery electrode group;
[0045] The battery electrode group includes the positive electrode sheet as described above, the ion conductor separator and the negative electrode sheet as described above;
[0046] An ion conductor diaphragm is located between the positive electrode sheet and the negative electrode sheet;
[0047] The battery electrode group is injected with electrolyte;
[0048] An ion conductor membrane comprising a base membrane, a first coating layer, and a second coating layer;
[0049] The first coating layer and the second coating layer are respectively located on the surface of the base film close to the positive electrode sheet and the surface of the base film close to the negative electrode;
[0050] Base film, including any one of polyethylene base film, polyethylene non-woven base film, polypropylene base film, polypropylene non-woven base film, polypropylene composite base film, polyimide base film, polyimide non-woven base film, polytetrafluoroethylene base film, polytetrafluoroethylene non-woven base film, polyvinyl chloride base film and polyvinyl chloride non-woven base film;
[0051] The first coating is a ceramic coating, which includes ceramic powder and an aqueous emulsion binder of an acrylate system;
[0052] In the ceramic coating, the mass percentage of the ceramic powder is 90%-99%, and the mass percentage of the binder is 1%-10%;
[0053] The ceramic powder used in the ceramic coating includes at least one of aluminum oxide, zirconium oxide, boehmite, magnesium hydroxide, barium sulfate, silicon oxide, aluminum nitride, magnesium oxide, titanium dioxide, yttrium oxide and cerium oxide;
[0054] The second coating is a fast ion conductor coating, which includes fast ion conductor powder and an acrylic acid aqueous emulsion binder;
[0055] In the fast ion conductor coating, the mass percentage of the fast ion conductor powder is 90%-99%, and the mass percentage of the binder is 1%-10%;
[0056] The fast ion conductor powder used in the fast ion conductor coating includes LATP powder or LLTO powder.
[0057] In addition, the present invention also provides a method for preparing the positive electrode sheet as described above, comprising the following steps:
[0058] The first step is to prepare a porous composite foil material of a positive electrode plate with a mixed primer coating: a conductive agent, an oxide solid electrolyte and a binder are mixed and stirred uniformly according to a preset mass percentage, and then dissolved in a solvent NMP for dispersion to obtain a mixed primer coating slurry, and the solid content of the mixed primer coating slurry is adjusted to 10-30% or the slurry viscosity is adjusted to 1000-4000cp by adjusting the amount of added solvent, and then a layer of mixed primer coating slurry is coated on the upper and lower sides of the composite porous aluminum foil current collector as described above, respectively, and dried at a temperature of 80°C-120°C. After drying, a porous composite foil material of a positive electrode plate with a mixed primer coating is obtained, that is, a composite porous aluminum foil;
[0059] In the first step, the preset mass percentages among the conductive agent, the oxide solid electrolyte and the binder are as follows:
[0060] 10%-40% of conductive agent, 50%-85% of oxide solid electrolyte and 5%-10% of binder, that is, the mass percentage of each component included in the solute of the mixed primer slurry;
[0061] The second step is to prepare the positive electrode material slurry: the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder are mixed and stirred uniformly according to a preset mass ratio, and then dissolved in the solvent NMP for dispersion to obtain the positive electrode material slurry, and the solid content of the positive electrode material slurry is adjusted to 60-75% or the slurry viscosity is adjusted to 6000-8000cp by adjusting the amount of added solvent;
[0062] In the second step, in a specific implementation, the mass ratio of the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (84-96):(1-5):(1-5):(2-6);
[0063] In the third step, the positive electrode material slurry obtained in the second step is coated on the upper and lower sides of the composite porous aluminum foil obtained in the first step, and dried at a temperature of 80°C-120°C. After drying, the positive electrode sheet is rolled to obtain a rolled positive electrode sheet, and then the rolled positive electrode sheet is cut to a specified size to finally obtain a finished positive electrode sheet.
[0064] In addition, the present invention also provides a method for preparing the negative electrode sheet as described above, comprising the following steps:
[0065] The first step is to prepare a porous composite foil material of a negative electrode plate with a mixed primer coating: a conductive agent, an oxide solid electrolyte and a binder are mixed and stirred uniformly according to a preset mass percentage, and then dissolved in a solvent deionized water for dispersion to obtain a mixed primer coating slurry, and by adjusting the amount of added solvent, the solid content of the mixed primer coating slurry is adjusted to 10-30% or the slurry viscosity is adjusted to 1000-4000cp, and then, a layer of mixed primer coating slurry is coated on the upper and lower sides of the composite porous copper foil current collector as described above, respectively, and dried at a temperature of 80°C-120°C. After drying, a porous composite foil material of a negative electrode plate with a mixed primer coating is obtained, that is, a composite porous aluminum foil;
[0066] In the first step, the preset mass percentages among the conductive agent, the oxide solid electrolyte and the binder are as follows:
[0067] 10%-40% conductive agent, 50%-85% oxide solid electrolyte and 5%-10% binder;
[0068] The second step is to prepare the negative electrode material slurry: the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder are mixed and stirred evenly according to a preset mass ratio, and then dissolved in a solvent deionized water for dispersion to obtain the negative electrode material slurry, and the solid content of the negative electrode material slurry is adjusted to 40-50% or the slurry viscosity is adjusted to 3000-5000cp by adjusting the amount of added solvent;
[0069] In the second step, in a specific implementation, the mass ratio of the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (83-97):(1-5):(1-5):(1-7);
[0070] In the third step, the negative electrode material slurry obtained in the second step is coated on the upper and lower sides of the composite porous copper foil obtained in the first step, and dried at a temperature of 80°C-120°C. After drying, it is rolled to obtain a rolled negative electrode sheet, and then the rolled negative electrode sheet is cut to a specified size to finally obtain a finished negative electrode sheet.
[0071] In addition, the present invention also provides a method for preparing a semi-solid lithium ion battery, comprising the following steps:
[0072] The first step is to stack and assemble the positive electrode sheet, the ion conductor separator and the negative electrode sheet in sequence, and then inject the electrolyte after packaging to prepare a soft-pack, round or square, semi-solid lithium-ion battery;
[0073] In the second step, the semi-solid lithium-ion battery is subjected to static standing, fixture pre-charging, degassing, formation, aging and capacity division processes to complete the battery preparation and basic electrical performance testing.
[0074] It can be seen from the technical solution provided by the present invention that, compared with the prior art, the present invention provides a porous composite foil, a positive electrode sheet, a negative electrode sheet and a semi-solid lithium ion battery and a preparation method, which are scientifically designed. Aiming at the problem of large internal resistance of the original composite foil, a mixed primer layer containing a conductive agent and an inorganic oxide solid electrolyte with good electronic conduction and ion conduction is introduced on the surface of the porous composite foil to improve the adhesion of the active material and the current collector, construct a complete ion and electron transmission channel, improve the electronic conduction and lithium ion migration efficiency, inhibit battery polarization, reduce thermal effects, reduce battery internal resistance, and improve rate performance, which has great practical significance.
[0075] In addition, in the present invention, by introducing solid electrolytes into the positive and negative porous composite foils, positive and negative electrode materials, positive and negative electrode material layers and diaphragms, the introduction of solid electrolyte materials can effectively reduce the amount of liquid electrolyte in the semi-solid battery system, further improving the safety performance of high specific energy batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 A schematic diagram of the cross-sectional structure of a porous composite foil provided by the present invention when not coated with a mixed primer layer, that is, a schematic diagram of the cross-sectional structure of a porous composite foil current collector;
[0077] Figure 2 A schematic diagram of a top view structure of a porous composite foil provided by the present invention when not coated with a mixed primer layer, that is, a schematic diagram of a top view structure of a porous composite foil current collector;
[0078] Figure 3 A schematic diagram of the cross-sectional structure of a positive electrode sheet provided by the present invention;
[0079] Figure 4 A schematic diagram of the cross-sectional structure of a negative electrode sheet provided by the present invention;
[0080] Figure 5 A schematic diagram of the cross-sectional structure of a battery electrode group of a semi-solid lithium-ion battery provided by the present invention. DETAILED DESCRIPTION
[0081] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation modes.
[0082] See also Figure 1 , Figure 2 , the present invention provides a porous composite foil material, which is applied to battery pole pieces (battery pole pieces include positive pole pieces and negative pole pieces), and includes a porous composite foil material current collector;
[0083] The porous composite foil current collector comprises a polymer insulating layer 102 and two metal conductive layers 101;
[0084] The upper and lower sides of the polymer insulating layer 102 are respectively covered with a layer of the metal conductive layer 101;
[0085] The porous composite foil current collector is provided with a plurality of through holes 103;
[0086] It should be noted that each through hole 103 vertically penetrates through a polymer insulating layer 102 and two metal conductive layers 101 on both sides of the polymer insulating layer 102 .
[0087] The outer side surface of each metal conductive layer 101 in the porous composite foil current collector is coated with a layer of mixed primer layer 104 .
[0088] In the present invention, in a specific implementation, the material of the polymer insulating layer 102 includes any one of polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polyimide (PI), polyacrylonitrile (PAN) and polyethylene terephthalate (PET);
[0089] In the present invention, in a specific implementation, the thickness of the polymer insulating layer 102 is 2-10 μm;
[0090] The thickness of each metal conductive layer 101 is 1-5 μm.
[0091] In the present invention, in specific implementation, when the porous composite foil current collector is applied to the positive electrode sheet, the two metal conductive layers 101 are both aluminum foils, and the porous composite foil current collector at this time is defined as a composite porous aluminum foil current collector;
[0092] When the porous composite foil current collector is used in the negative electrode plate, the two metal conductive layers 101 are both copper foils, and the porous composite foil current collector at this time is defined as a composite porous copper foil current collector.
[0093] In the present invention, the metal conductive layer is compounded on both sides of the polymer insulating layer 102. Compounding on both sides of the polymer insulating layer means coating on both sides of the polymer insulating layer. Specifically, the metal conductive layer is coated on both sides of the polymer insulating layer by evaporation, sputtering, chemical plating and other methods.
[0094] In the present invention, in a specific implementation, the shape of the through hole 103 may include at least one of a circle, an ellipse, a diamond and a triangle, and may be other polygons.
[0095] In the present invention, in a specific implementation, the aperture of the through hole 103 is between 0.2-3 μm;
[0096] In the present invention, in a specific implementation, the porosity of the porous composite foil current collector is 10%-40%.
[0097] In the present invention, in a specific implementation, the method for forming the through hole 103 includes any one of punching, pressing and laser etching.
[0098] In the present invention, in a specific implementation, the mixed primer layer 104 includes the following components expressed in mass percentage:
[0099] 10%-40% conductive agent, 50%-85% oxide solid electrolyte and 5%-10% binder.
[0100] In a specific implementation, the prepared mixed undercoat slurry (the solute of the mixed undercoat slurry includes a conductive agent, an oxide solid electrolyte and a binder. When the mixed undercoat is used to prepare a positive electrode sheet, the solvent is NMP. When the mixed undercoat is used to prepare a negative electrode sheet, the solvent is deionized water. The solid content of the mixed undercoat slurry is 10%-30%, and the slurry viscosity is 1000-4000cp) is applied on the porous composite foil.
[0101] In a specific implementation, the thickness of each layer of the mixed primer layer 104 is 2-10 microns;
[0102] In a specific implementation, for the mixed primer layer 104, the conductive agent includes at least one of carbon black, Ketjen black, conductive graphite, conductive fiber, carbon nanotube and graphene;
[0103] An oxide solid electrolyte comprising at least one of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO) and lithium lanthanum zirconium thallium oxide (LLZTO);
[0104] The binder includes one or a mixture of two or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), acrylic acid (AA), polyethylene oxide (PEO), sodium carboxymethylcellulose (PTFE), styrene butadiene rubber (SBR), hydroxypropyl methylcellulose (HPMC), carboxy styrene butadiene latex (XSBRL) and polyvinyl alcohol (PVA), that is, at least one;
[0105] See also Figure 3 , the present invention also provides a positive electrode plate, which includes the porous composite foil as described above;
[0106] The outer side of each mixed primer layer 104 in the porous composite foil is coated with a positive electrode material layer 105 (i.e., a positive electrode active material layer);
[0107] See also Figure 4 , the present invention also provides a negative electrode plate, which includes the porous composite foil as described above;
[0108] The outer side of each mixed primer layer 104 in the porous composite foil is coated with a negative electrode material layer 205 (i.e., a negative electrode active material layer);
[0109] In the present invention, in specific implementation, the positive electrode material layer 105 includes a positive electrode active material, an oxide solid electrolyte, a conductive agent and a binder;
[0110] The mass ratio of the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (84-96):(1-5):(1-5):(2-6);
[0111] Wherein, for the positive electrode material layer 105, the positive electrode active material specifically includes at least one of lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium iron phosphate (LFP) and lithium manganese iron phosphate (LMFP);
[0112] It should be noted that the positive electrode active material refers to at least one of lithium cobalt oxide (LCO), lithium manganese oxide (LMO), nickel cobalt manganese oxide (NCM), nickel cobalt aluminum oxide (NCA), lithium iron phosphate (LFP) and lithium manganese iron phosphate (LMFP). The surface of these materials can be coated with a solid electrolyte (that is, coated with an oxide solid electrolyte located outside the positive electrode active material). It is a core-shell structure material, and the solid electrolyte is the outer coating layer.
[0113] For the positive electrode material layer 105, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers and graphene;
[0114] For the positive electrode material layer 105, the oxide solid electrolyte includes at least one of LATP, LAGP, LLZO, LLTO and LLZTO;
[0115] For the positive electrode material layer 105 , the binder includes at least one of PVDF, SBR, CMC and PTFE.
[0116] In specific implementation, the surface density of the positive electrode material layer 105 is 10-50 mg / cm 2 .
[0117] In the present invention, in specific implementation, the negative electrode material layer 205 includes a negative electrode active material, an oxide solid electrolyte, a conductive agent and a binder;
[0118] The mass ratio of the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (83-97):(1-5):(1-5):(1-7).
[0119] Wherein, for the negative electrode material layer 205, the negative electrode active material includes one or more of silicon, silicon dioxide, silicon oxide, artificial graphite, natural graphite, composite graphite, soft carbon and hard carbon;
[0120] For the negative electrode material layer 205, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers and graphene;
[0121] For the negative electrode material layer 205, the oxide solid electrolyte includes at least one of LATP, LAGP, LLZO, LLTO and LLZTO;
[0122] For the negative electrode material layer 205 , the binder includes any one of SBR, PAA and PTFE.
[0123] In specific implementation, the surface density of the negative electrode material layer 205 is 5-30 mg / cm 2 ;
[0124] See also Figure 5 , the present invention also provides a semi-solid lithium ion battery, which includes a battery electrode group;
[0125] The battery electrode group includes the positive electrode sheet 1 as described above, the ion conductor separator 3 and the negative electrode sheet 2 as described above;
[0126] An ion conductor separator 3 is located between the positive electrode sheet 1 and the negative electrode sheet 2;
[0127] The battery electrode group is injected with electrolyte; that is, the electrolyte fills the gap between the positive electrode plate 1, the ion conductor separator 3 and the negative electrode plate 2;
[0128] The ion conductor membrane 3 includes a base membrane 301, a first coating 302 and a second coating 303;
[0129] The first coating layer and the second coating layer are respectively located on the surface of the base film close to the positive electrode plate and the surface of the base film close to the negative electrode. Figure 5 the upper and lower side surfaces shown;
[0130] Base film, including any one of polyethylene base film, polyethylene non-woven base film, polypropylene base film, polypropylene non-woven base film, polypropylene / polyethylene / polypropylene (PP / PE / PP) composite base film, polyimide (PI) base film, polyimide non-woven base film, polytetrafluoroethylene (PTFE) based film, polytetrafluoroethylene non-woven base film, polyvinyl chloride (PVC) base film and polyvinyl chloride non-woven base film;
[0131] The first coating is a ceramic coating, and the ceramic powder used in the ceramic coating includes at least one of aluminum oxide, zirconium oxide, boehmite, magnesium hydroxide, barium sulfate, silicon oxide, aluminum nitride, magnesium oxide, titanium dioxide, yttrium oxide and cerium oxide (all of these materials are powders);
[0132] In specific implementation, the ceramic coating includes ceramic powder and an aqueous emulsion binder of an acrylate system;
[0133] In the ceramic coating, the mass percentage of ceramic powder is 90%-99%, and the mass percentage of binder is 1%-10%. It should be noted that the ceramic coating diaphragm is a lithium battery diaphragm that is maturely applied in the existing battery industry.
[0134] In specific implementation, the particle size of the ceramic powder is 0.01-2um.
[0135] The second coating is a fast ion conductor coating, and the fast ion conductor powder (also called solid electrolyte) used in the fast ion conductor coating includes LATP powder or LLTO powder;
[0136] In specific implementation, the fast ion conductor coating includes fast ion conductor powder and acrylic acid aqueous emulsion binder;
[0137] In the fast ion conductor coating, the mass percentage of the fast ion conductor powder is 90%-99%, and the mass percentage of the binder is 1%-10%.
[0138] In specific implementation, the particle size of the fast ion conductor powder is 0.01-2um, so as to avoid affecting the density and bonding effect of the coating due to the large particle size, and at the same time avoid affecting ion transmission.
[0139] In the present invention, in a specific implementation, the thickness of the ceramic coating is 0.1-5 μm;
[0140] In the present invention, in a specific implementation, the electrolyte comprises a lithium salt, a solvent and an additive;
[0141] The lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2) and lithium difluorooxalatoborate (LiDFOB).
[0142] The solvent comprises at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), phthalate (DMP), dimethyl maleate (DMM), ethylene glycol dimethyl ether (DME) and tetrahydrofuran (TH)F;
[0143] The additive includes at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), propane sultone (PS), propene sultone (PST), diethylene sulfate (DTD), and difluoroethylene carbonate (DFEC).
[0144] In terms of specific implementation, the electrolyte injection volume of each semi-solid-state battery is 0.5-1.5g / Ah;
[0145] In a specific implementation, the molar concentration of the lithium salt is 0.5-2 mol / L;
[0146] In the present invention, in a specific implementation, the semi-solid-state battery is a soft-pack semi-solid-state battery prepared by a lamination process.
[0147] In addition, the present invention also provides a method for preparing a positive electrode sheet, comprising the following steps:
[0148] The first step is to prepare a porous composite foil material of a positive electrode plate with a mixed primer coating: a conductive agent, an oxide solid electrolyte and a binder are mixed and stirred uniformly according to a preset mass percentage, and then dissolved in a solvent NMP for dispersion to obtain a mixed primer coating slurry, and by adjusting the amount of added solvent, the solid content of the mixed primer coating slurry is adjusted to 10-30% or the slurry viscosity is adjusted to 1000-4000cp, and then, a layer of mixed primer coating slurry is coated on the upper and lower sides of the composite porous aluminum foil current collector as described above, respectively, and dried at a temperature of 80°C-120°C (put in an oven), and after drying, a porous composite foil material of a positive electrode plate with a mixed primer coating is obtained, that is, a composite porous aluminum foil;
[0149] In the first step, in specific implementation, the preset mass percentages between the conductive agent, the oxide solid electrolyte and the binder are as follows:
[0150] 10%-40% of conductive agent, 50%-85% of oxide solid electrolyte and 5%-10% of binder, that is, the mass percentage of each component included in the solute of the mixed primer slurry.
[0151] The second step is to prepare the positive electrode material slurry: the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder are mixed and stirred uniformly according to a preset mass ratio, and then dissolved in the solvent NMP for dispersion to obtain the positive electrode material slurry, and the solid content of the positive electrode material slurry is adjusted to 60-75% or the slurry viscosity is adjusted to 6000-8000cp by adjusting the amount of added solvent;
[0152] In the second step, in specific implementation, the mass ratio between the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (84-96):(1-5):(1-5):(2-6).
[0153] In the third step, the positive electrode material slurry obtained in the second step is coated on the upper and lower sides of the composite porous aluminum foil obtained in the first step, and dried at a temperature of 80°C-120°C (put in an oven), and then rolled after drying to obtain a rolled positive electrode sheet, and then the rolled positive electrode sheet is cut to a specified size to finally obtain a finished positive electrode sheet.
[0154] In addition, the present invention also provides a method for preparing a negative electrode sheet, comprising the following steps:
[0155] The first step is to prepare a porous composite foil material of a negative electrode plate with a mixed primer coating: a conductive agent, an oxide solid electrolyte and a binder are mixed and stirred uniformly according to a preset mass percentage, and then dissolved in a solvent deionized water for dispersion to obtain a mixed primer coating slurry, and by adjusting the amount of added solvent, the solid content of the mixed primer coating slurry is adjusted to 10-30% or the slurry viscosity is adjusted to 1000-4000cp, and then, a layer of mixed primer coating slurry is coated on the upper and lower sides of the composite porous copper foil current collector as described above, respectively, and dried at a temperature of 80°C-120°C (put in an oven), and after drying, a porous composite foil material of a negative electrode plate with a mixed primer coating is obtained, that is, a composite porous aluminum foil;
[0156] In the first step, in specific implementation, the preset mass percentages between the conductive agent, the oxide solid electrolyte and the binder are as follows:
[0157] 10%-40% of conductive agent, 50%-85% of oxide solid electrolyte and 5%-10% of binder, that is, the mass percentage of each component included in the solute of the mixed primer slurry.
[0158] The second step is to prepare the negative electrode material slurry: the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder are mixed and stirred evenly according to a preset mass ratio, and then dissolved in a solvent deionized water for dispersion to obtain the negative electrode material slurry, and the solid content of the negative electrode material slurry is adjusted to 40-50% or the slurry viscosity is adjusted to 3000-5000cp by adjusting the amount of added solvent;
[0159] In the second step, in specific implementation, the mass ratio between the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (83-97):(1-5):(1-5):(1-7).
[0160] In the third step, the negative electrode material slurry obtained in the second step is coated on the upper and lower sides of the composite porous copper foil obtained in the first step, and dried at a temperature of 80°C-120°C (put in an oven), and then rolled after drying to obtain a rolled negative electrode sheet, and then the rolled negative electrode sheet is cut to a specified size to finally obtain a finished negative electrode sheet.
[0161] In addition, the present invention provides a method for preparing a semi-solid lithium ion battery, comprising the following steps:
[0162] The first step is to stack and assemble the previously prepared positive electrode sheet, ion conductor separator and previously prepared negative electrode sheet in sequence (i.e., assemble them using the existing stacking process), and then inject electrolyte after packaging (e.g., packaging by aluminum-plastic film) to prepare a soft-pack, round or square, semi-solid lithium-ion battery;
[0163] In the second step, the semi-solid lithium-ion battery is subjected to conventional (i.e. existing) static, fixture pre-charging, degas (degassing), formation, aging and capacity separation processes to complete the preparation of the battery and basic electrical performance testing;
[0164] Among them, the pressure of fixture pre-charging, formation and volume separation is 500-1500kgf, the temperature is 25-45℃, and the ratio is 0.1C-1C.
[0165] It should be noted that the operations of fixture pre-charging, formation and capacity division used in the present invention are conventional operations in the battery charging and discharging process of the lithium battery industry and will not be described in detail here.
[0166] It should be noted that, for the technical solution of the present invention, a mixed bottom coating containing a conductive agent and an inorganic oxide solid electrolyte with good electronic and ionic conduction is introduced on the porous composite foil to improve the adhesion between the positive and negative electrode slurries and the current collector foil, and a complete ion and electron transmission channel is constructed between the active material in the pole piece and the current collector foil, thereby reducing the impedance of the pole piece and improving the performance of the battery. At the same time, by introducing solid electrolytes into the positive and negative porous composite foils, the positive and negative electrode materials, the positive and negative electrode material layers and the diaphragm, a good ion diffusion network is established, which can effectively reduce the amount of liquid electrolyte in the semi-solid battery and further improve the safety performance of the battery.
[0167] It should be noted that semi-solid-state batteries are a compromise between liquid lithium-ion batteries and all-solid-state lithium batteries. The mass or volume of the solid electrolyte in the monomer accounts for half of the total mass or volume of the electrolyte in the monomer. In comparison, the solid electrolyte in the semi-solid-state battery is non-flammable, high-temperature resistant, non-corrosive, and non-volatile, and the amount of liquid electrolyte is greatly reduced. Therefore, when damage or puncture occurs, spontaneous combustion or explosion will be effectively avoided.
[0168] In order to more clearly understand the technical solution of the present invention, the technical solution of the present invention is described below through specific embodiments.
[0169] Example
[0170] 1. Prepare the positive electrode.
[0171] First, 30% by mass of conductive carbon black, 60% of solid electrolyte LATP and 10% of binder PVDF are added to solvent NMP to obtain a mixed primer slurry, the solid content of the slurry is adjusted to 20% and the viscosity is 3000cp, and the prepared mixed primer slurry is applied to the holes and both sides of a porous composite aluminum foil with a thickness of 12μm (wherein the thickness of the PET layer is 9μm, the thickness of the surface aluminum metal layer as the metal conductive layer is 1.5μm, the aperture of the circular through hole is 1μm, and the porosity is 20%), and then dried at 90°C to obtain a composite porous aluminum foil with a mixed primer;
[0172] Then, 90% by mass of the positive electrode active material (specifically, ternary NCM coated with LATP surface, Ni% = 90%), 3% of the solid electrolyte LATP, 3% of the conductive agent Super P and 4% of the binder PVDF were mixed to prepare the positive electrode material slurry;
[0173] Then, the positive electrode material slurry was coated on both sides of the composite porous aluminum foil with the mixed primer layer, and the positive electrode coating surface density was 40 mg / cm 2 After drying, rolling and cutting, the positive electrode sheet is obtained.
[0174] like Figure 1 and Figure 2 When the porous composite foil is a porous composite aluminum foil, the polymer insulating layer 102 included in the foil is a PET layer, the metal conductive layers 101 on both sides of the polymer insulating layer 102 are aluminum metal layers (i.e., aluminum foil), and a plurality of through holes 103 are provided on the porous composite aluminum foil;
[0175] See also Figure 3 As shown, the positive electrode plate comprises a porous composite aluminum foil having a layer of mixed primer layer 104 on the upper and lower sides, and a layer of positive electrode material layer 105 is coated on the outer side of each mixed primer layer 104;
[0176] 2. Prepare the negative electrode sheet.
[0177] First, 30% by mass of conductive carbon black, 60% of solid electrolyte LATP, 5% of binder SBR and 5% of CMC were mixed evenly, deionized water was added to obtain a mixed primer slurry, the solid content of the slurry was adjusted to 20% and the viscosity was 2000cp, and the prepared mixed slurry was applied to the holes and both sides of a 6.5μm thick porous composite copper foil (wherein the PET layer has a thickness of 4.5μm, the surface copper metal layer as the metal conductive layer has a thickness of 1μm, the aperture of the circular through hole is 1μm, and the porosity is 20%), with a thickness of 3μm, and then dried at 90°C to obtain a composite porous copper foil with a mixed primer;
[0178] Then, 92% by mass of negative electrode active material (specifically, a mixture of graphite and silicon oxide coated on the surface of LATP), 3% of solid electrolyte LATP, 2% of conductive agent Super P and 3% of binder PAA are mixed to prepare negative electrode material slurry;
[0179] Then, the negative electrode material slurry was coated on both sides of the composite porous copper foil with the mixed primer layer, and the positive electrode coating surface density was 20 mg / cm 2 After drying, rolling and cutting, the negative electrode sheet is obtained.
[0180] See also Figure 4 As shown, the negative electrode plate includes a porous composite copper foil having a layer of mixed primer layer 104 on the upper and lower sides respectively, and a layer of negative electrode material layer 205 is coated on the outer side of each mixed primer layer 104 respectively.
[0181] 3. Preparation of semi-solid lithium-ion batteries.
[0182] First, the negative electrode sheet, ion conductor separator and positive electrode are stacked in sequence, and a soft-pack semi-solid battery is prepared through a lamination process, wherein the ion conductor separator is 16 μm thick, the PE base film is 12 μm thick, the surface close to the positive electrode is coated with an Al2O3 porcelain coating with a thickness of 2 μm, and the surface close to the negative electrode is coated with a LATP fast ion conductor coating with a thickness of 2 μm.
[0183] Then, the battery is packaged with aluminum-plastic film, and then the electrolyte is injected at a liquid injection coefficient of 1.5g / Ah, and the battery is placed at high temperature, pre-charged in a fixture, degassed, formed, aged, and divided in volume to complete the battery preparation and basic electrical performance test. The pre-charge, formation, and volume division are carried out under 1000kgf pressure, 25℃ ambient temperature, and 0.2C rate.
[0184] The schematic diagram of the structure of the semi-solid lithium-ion battery cell (i.e., battery electrode group) is as follows Figure 5 As shown, it includes a positive electrode sheet 1, a negative electrode sheet 2, and an ion conductor membrane 3.
[0185] The battery electrode group includes the positive electrode sheet 1 as described above, the ion conductor separator 3 and the negative electrode sheet 2 as described above;
[0186] An ion conductor separator 3 is located between the positive electrode sheet 1 and the negative electrode sheet 2;
[0187] The battery electrode group is injected with electrolyte; that is, the electrolyte fills the gap between the positive electrode plate 1, the ion conductor separator 3 and the negative electrode plate 2;
[0188] The ion conductor membrane 3 includes a base film 301, a surface coating close to the positive electrode side (ie, a first coating 302), and a surface coating close to the negative electrode side (ie, a second coating 30).
[0189] Comparative example 1.
[0190] Comparative Example 1 is substantially the same as Example 1, except that:
[0191] 1. The positive electrode material slurry is directly coated on both sides of the 12μm thick PET composite aluminum foil (i.e. composite porous aluminum foil), and the negative electrode material slurry is directly coated on both sides of the 6μm thick PET composite copper foil;
[0192] 2. The electrolyte is injected into the battery cell at an injection rate of 2.0 g / Ah. The rest is the same as the preparation process of the embodiment.
[0193] Comparative Example 2:
[0194] Comparative Example 2 is substantially the same as Example 1, except that:
[0195] 1. The positive electrode material slurry is directly coated on both sides of the 12μm thick porous PET composite aluminum foil, and the negative electrode slurry is directly coated on both sides of the 6μm thick porous PET composite copper foil;
[0196] 2. The electrolyte is injected into the battery cell at an injection rate of 2.0 g / Ah. The rest is the same as the preparation process of the embodiment.
[0197] The energy density, internal resistance and rate performance of the embodiment and two comparative examples are compared. The comparison results are shown in Table 1.
[0198] Table 1:
[0199]
[0200] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0201] 1. The porous composite foil used in the present invention can reduce the weight proportion of the current collector in the battery and effectively improve the energy density of the battery;
[0202] 2. The present invention introduces a mixed bottom coating containing a conductive agent and an inorganic oxide solid electrolyte with good electronic and ion conduction into the pores and surface of the porous composite foil to construct a fast ion and electron transmission channel, which can inhibit battery polarization, reduce battery internal resistance, and improve rate performance;
[0203] 3. The present invention introduces solid electrolytes into the positive and negative porous composite foils, positive and negative active materials, positive and negative electrode material layers and diaphragms, thereby establishing a good ion diffusion network, which can effectively reduce the amount of liquid electrolyte in the semi-solid battery and further improve the safety performance of the battery.
[0204] In summary, compared with the prior art, the porous composite foil, positive electrode sheet, negative electrode sheet and semi-solid lithium ion battery and preparation method provided by the present invention are scientifically designed. To address the problem of large internal resistance of the original composite foil, a mixed primer layer containing a conductive agent and an inorganic oxide solid electrolyte with good electronic conduction and ion conduction is introduced on the surface of the porous composite foil to improve the adhesion between the active material and the current collector, construct a complete ion and electron transmission channel, improve the electronic conduction and lithium ion migration efficiency, inhibit battery polarization, reduce thermal effects, reduce battery internal resistance, and improve rate performance, which has great practical significance.
[0205] In addition, in the present invention, by introducing solid electrolytes into the positive and negative porous composite foils, positive and negative electrode materials, positive and negative electrode material layers and diaphragms, the introduction of solid electrolyte materials can effectively reduce the amount of liquid electrolyte in the semi-solid battery system, further improving the safety performance of high specific energy batteries.
[0206] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A semi-solid lithium-ion battery, characterized in that: Including battery pole group; The battery electrode group comprises a positive electrode sheet, an ion conductor diaphragm (3) and a negative electrode sheet; A positive electrode plate comprises a porous composite foil; the outer side of each mixed primer layer (104) in the porous composite foil is coated with a positive electrode material layer (105); A positive electrode material layer (105), comprising a positive electrode active material, an oxide solid electrolyte, a conductive agent and a binder; The mass ratio of the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (84-96):(1-5):(1-5):(2-6); A negative electrode plate comprises a porous composite foil; the outer side of each mixed primer layer (104) in the porous composite foil is coated with a negative electrode material layer (205); A negative electrode material layer (205), comprising a negative electrode active material, an oxide solid electrolyte, a conductive agent and a binder; The mass ratio of the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (83-97): (1-5): (1-5): (1-7); The porous composite foil is used in a battery pole piece and comprises a porous composite foil current collector; the porous composite foil current collector comprises a polymer insulating layer (102) and two metal conductive layers (101); A layer of the metal conductive layer (101) is respectively provided on the upper and lower sides of the polymer insulating layer (102) to cover the metal conductive layer (101); A plurality of through holes (103) are provided through the porous composite foil current collector; The outer side surface of each metal conductive layer (101) in the porous composite foil current collector is coated with a layer of mixed primer layer (104); A mixed primer layer (104) comprising the following components expressed in mass percentage: 10%-40% of a conductive agent, 50%-85% of an oxide solid electrolyte and 5%-10% of a binder; For the mixed primer (104), the conductive agent includes at least one of carbon black, Ketjen black, conductive graphite, conductive fiber, carbon nanotube and graphene; the oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide and lithium lanthanum zirconium thallium oxide; the binder includes one or a mixture of two or more of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, polyethylene oxide, carboxymethyl cellulose sodium, styrene butadiene rubber, hydroxypropyl methylcellulose, carboxystyrene butadiene latex and polyvinyl alcohol; The ion conductor diaphragm (3) is located between the positive electrode sheet and the negative electrode sheet.
2. The semi-solid lithium-ion battery according to claim 1, characterized in that: When the porous composite foil current collector is applied to the positive electrode plate, the two metal conductive layers (101) are both aluminum foils, and the porous composite foil current collector at this time is defined as a composite porous aluminum foil current collector; when the porous composite foil current collector is applied to the negative electrode plate, the two metal conductive layers (101) are both copper foils, and the porous composite foil current collector at this time is defined as a composite porous copper foil current collector.
3. The semi-solid lithium-ion battery according to claim 1, characterized in that: The polymer insulating layer (102) has a thickness of 2-10 μm; The thickness of each metal conductive layer (101) is 1-5 μm; The aperture of the through hole (103) is between 0.2-3 μm; The porosity of the porous composite foil current collector is 10%-40%; The thickness of each layer of the mixed primer layer (104) is 2-10 microns.
4. The semi-solid lithium-ion battery according to claim 1, characterized in that: The material of the polymer insulating layer (102) includes any one of polyethylene, polypropylene, polyvinyl chloride, polyimide, polyacrylonitrile and polyethylene terephthalate.
5. The semi-solid lithium-ion battery according to claim 1, characterized in that: The battery electrode group is injected with electrolyte; An ion conductor diaphragm (3) comprises a base film (301), a first coating (302) and a second coating (303); the first coating and the second coating are respectively located on a surface of the base film close to the positive electrode plate and a surface of the base film close to the negative electrode; The base film includes any one of a polyethylene base film, a polyethylene non-woven base film, a polypropylene base film, a polypropylene non-woven base film, a polypropylene composite base film, a polyimide base film, a polyimide non-woven base film, a polytetrafluoroethylene base film, a polytetrafluoroethylene non-woven base film, a polyvinyl chloride base film and a polyvinyl chloride non-woven base film; The first coating is a ceramic coating, which includes ceramic powder and an aqueous emulsion binder of an acrylate system; In the ceramic coating, the mass percentage of the ceramic powder is 90%-99%, and the mass percentage of the binder is 1%-10%; The ceramic powder used in the ceramic coating includes at least one of aluminum oxide, zirconium oxide, boehmite, magnesium hydroxide, barium sulfate, silicon oxide, aluminum nitride, magnesium oxide, titanium dioxide, yttrium oxide and cerium oxide; the second coating is a fast ion conductor coating, which includes fast ion conductor powder and an acrylic acid aqueous emulsion binder; In the fast ion conductor coating, the mass percentage of the fast ion conductor powder is 90%-99%, and the mass percentage of the binder is 1%-10%; The fast ion conductor powder used in the fast ion conductor coating includes LATP powder or LLTO powder.
6. The semi-solid lithium-ion battery according to claim 2, characterized in that: The method for preparing the positive electrode sheet comprises the following steps: The first step is to prepare a porous composite foil material for a positive electrode plate with a mixed primer coating: a conductive agent, an oxide solid electrolyte and a binder are mixed and stirred uniformly according to a preset mass percentage, and then dissolved in a solvent NMP for dispersion to obtain a mixed primer coating slurry, and by adjusting the amount of added solvent, the solid content of the mixed primer coating slurry is adjusted to 10-30% or the slurry viscosity is adjusted to 1000-4000cp, and then, a layer of mixed primer coating slurry is coated on the upper and lower sides of the composite porous aluminum foil current collector as described above, respectively, and dried at a temperature of 80°C-120°C. After drying, a porous composite foil material for a positive electrode plate with a mixed primer coating is obtained, i.e., a composite porous aluminum foil; in the first step, the preset mass percentages between the conductive agent, the oxide solid electrolyte and the binder are as follows: 10%-40% of the conductive agent, 50%-85% of the oxide solid electrolyte and 5%-10% of the binder.
7. The semi-solid lithium-ion battery according to claim 2, characterized in that: The method for preparing the negative electrode sheet comprises the following steps: The first step is to prepare a porous composite foil material of a negative electrode plate with a mixed primer coating: a conductive agent, an oxide solid electrolyte and a binder are mixed and stirred uniformly according to a preset mass percentage, and then dissolved in a solvent deionized water for dispersion to obtain a mixed primer coating slurry, and by adjusting the amount of added solvent, the solid content of the mixed primer coating slurry is adjusted to 10-30% or the slurry viscosity is adjusted to 1000-4000cp, and then, a layer of mixed primer coating slurry is coated on the upper and lower sides of the composite porous copper foil current collector as described above, respectively, and dried at a temperature of 80°C-120°C. After drying, a porous composite foil material of a negative electrode plate with a mixed primer coating is obtained, that is, a composite porous aluminum foil; In the first step, the preset mass percentages among the conductive agent, the oxide solid electrolyte and the binder are specifically as follows: 10%-40% of the conductive agent, 50%-85% of the oxide solid electrolyte and 5%-10% of the binder; The second step is to prepare the negative electrode material slurry: the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder are mixed and stirred evenly according to a preset mass ratio, and then dissolved in a solvent deionized water for dispersion to obtain the negative electrode material slurry, and the solid content of the negative electrode material slurry is adjusted to 40-50% or the slurry viscosity is adjusted to 3000-5000cp by adjusting the amount of added solvent; In the second step, in a specific implementation, the mass ratio of the negative electrode active material, the oxide solid electrolyte, the conductive agent and the binder is (83-97):(1-5):(1-5):(1-7); In the third step, the negative electrode material slurry obtained in the second step is coated on the upper and lower sides of the composite porous copper foil obtained in the first step, and dried at a temperature of 80°C-120°C. After drying, it is rolled to obtain a rolled negative electrode sheet, and then the rolled negative electrode sheet is cut to a specified size to finally obtain a finished negative electrode sheet.
8. A method for preparing a semi-solid lithium ion battery according to any one of claims 1 to 7, characterized in that: The following steps are involved: The first step is to stack and assemble the positive electrode plate, the ion conductor separator and the negative electrode plate in sequence, and then inject the electrolyte after packaging to prepare a soft-pack, round or square, semi-solid lithium-ion battery; the second step is to subject the semi-solid lithium-ion battery to static, fixture pre-charging, degassing, formation, aging and capacity division processes in sequence to complete the preparation of the battery and basic electrical performance testing.
Citation Information
Patent Citations
Composite pole plate of lithium ion battery and preparation method of composite pole plate
CN105633340A
Solid electrolyte coating based on positive electrode protection, positive plate and preparation method
CN111987373A
Ternary positive pole piece for lithium battery with high safety and high capacity as well as preparation method and application of ternary positive pole piece
CN113745456A
Lithium battery composite diaphragm as well as preparation method and application thereof
CN114464960A
Negative plate for lithium battery as well as preparation method and application of negative plate
CN114639868A
Cited By
Composite current collector and preparation method and application thereof
CN117080454A